2003
DOI: 10.1200/jco.2003.02.147
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Escalating-Dose Irinotecan Given Weekly With Cisplatin and Concurrent Radiotherapy in Locally Advanced Esophageal Cancer

Abstract: Cisplatin, irinotecan, and concurrent radiotherapy can be administered on a convenient schedule with relatively minimal toxicity and an acceptable rate of complete response in esophageal cancer. Further phase II evaluation of this regimen is ongoing. A phase III comparison to fluorouracil or taxane-containing chemoradiotherapy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
46
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 25 publications
5
46
2
1
Order By: Relevance
“…This result, together with that of others, seems to imply that surgical resection could be useful at least in some patients (Adelstein et al, 2000;Ilson et al, 2003). No conclusions can be drawn on the utility of HDR-EBT in the local control of disease from our data, as few patients received this treatment.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This result, together with that of others, seems to imply that surgical resection could be useful at least in some patients (Adelstein et al, 2000;Ilson et al, 2003). No conclusions can be drawn on the utility of HDR-EBT in the local control of disease from our data, as few patients received this treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…A change in the chemotherapy schedule, like the use of weekly doses, might help to reduce the acute tumour necrosis and permit wall repair (Ilson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have from our institution have also indicated that using non-5-FU containing chemotherapy regimens with concurrent radiotherapy may also have a potential to lower toxicity of combined chemoradiotherapy. In two phase I trials combining either weekly paclitaxel (Brenner et al, 2004) or weekly irinotecan (Ilson et al, 2003) with a weekly schedule of relative low-dose cisplatin and concurrent radiotherapy, gastrointestinal, and haematologic toxicities were relatively mild. These regimens also offer promise as an alternative to conventional 5-FU and cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is to our knowledge the first phase II trial evaluating in a population of inoperable patients with the regimen defined in phase I (Ilson et al, 2003). The main results of the present study were the complete clinical response rate of 58.1% (95% CI, 43.4 -72.8%), overall survival rate of 27.9% (95% CI: 13.4 -41.3%) at 2 years and the absence of significant improvement of dysphagia after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I -II studies of weekly irinotecan and radiation therapy have been performed (Koukourakis et al, 1999;Takeda et al, 1999). Recently, phase I study of weekly with cisplatin -irinotecan chemotherapy followed by chemo-radiotherapy in locally advanced oesophageal cancer has been reported (Ilson et al, 2003). The dose-limiting toxicity was primarily myelosuppression, no grade 3 or 4 oesophagitis, diarrhoea or stomatitis was observed.…”
mentioning
confidence: 99%